KNOWLEDGE CREATION: PERSPECTIVE ON THE HALAL SMEs IN SIDOARJO - Novie, Muhafidhah; Mahmudah, Siti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine of knowledge creation as perspective on the Halal SMEs in Jabon District, Sidoarjo. To get a clear and structured picture of the phenomenon under study, the research was conducted using a descriptive qualitative method through an ethnomethodological approach. The informants were selected using a purposive sampling technique by considering that the informants are members of the Seaweed SME, namely entrepreneurs (Source Mulyo Cooperative 5758) and red seaweed farmers of Gracilaria sp. The results showed that the knowledge creation as perspective on the Halal Seaweed SMEs in Jabon District, Sidoarjo could be done by applying the SECI Nonaka and Takeuchi models. This model emphasizes the creation of new knowledge in the organization through the conversion of tacit and explicit knowledge with the dimensions of Socialization, Externalization, Combination, and Internalization. This will form a loop that will never stop, and will even expand. Through this continuous process, it is hoped that the differences in understanding between Cooperatives and Farmers regarding the development of seaweed SME will be corrected, resulting in the same agreement on efforts to develop Seaweed SMEs based on knowledge creation perspective.